Unraveling atmosphere and sea ice in the Arctic : advancements in a multi-parameter retrieval using satellite microwave radiometer data ... - Rückert, Janna Elisabeth (Universität Bremen, 2024)
The Arctic undergoes accelerated warming compared to Global Warming, known as Arctic amplification. To understand this phenomenon, studying key variables at various scales is crucial. Every day, satellite radiometers measure Arctic-wide emissions of microwave radiation in terms of brightness temperatures. We use the distinct sensitivities of observations at different frequencies to atmospheric and surface parameters, aiming to disentangle the satellite signal and improve a multi-parameter retrieval. The retrieval involves inverting a forward model with an optimal estimation method to attribute satellite measurements (6.9 to 89 GHz) to a specific geophysical state. For that, surface emissions need to be well represented in the forward model. We study surface emissions by considering the theoretical concept of emissivity followed by an analysis of brightness temperature measurements and derived emissivities that we obtained during a summer ship campaign. In a case study, we examine the impact of changing ...